2012
DOI: 10.1017/s0025315412000410
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variation of south-western Atlantic clamMactra isabelleana(Bivalvia: Mactridae)

Abstract: The phenotypic shell shape variation of Mactra isabelleana was tested using the geometric morphometric method. Four localities were sampled along the Río de la Plata estuary and the coast of Buenos Aires province. Principal component analysis and canonical variates analysis of the first principal components were performed to reveal the shell variation and differences among localities, respectively. The specimens from different microhabitats mostly overlapped, although differences in shape were observed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Land snails are sensitive to environmental conditions and several studies have shown that interaction with the environment affects their shell's characteristics (Chiba, 2004;Carvajal-Rodríguez et al, 2005;Signorelli, Márquez, & Pastorino, 2012). In the current study, it seems altitude is a factor than can determine morphometric differences.…”
Section: Discussionmentioning
confidence: 99%
“…Land snails are sensitive to environmental conditions and several studies have shown that interaction with the environment affects their shell's characteristics (Chiba, 2004;Carvajal-Rodríguez et al, 2005;Signorelli, Márquez, & Pastorino, 2012). In the current study, it seems altitude is a factor than can determine morphometric differences.…”
Section: Discussionmentioning
confidence: 99%
“…This method is successful in determining the number of groups in a hierarchical cluster analyses. The graphical output of the MDGC test is also a useful tool because it shows a clear distinction between statistically different shell shapes of mollusk bivalves from each locality, as well as their relationships (Márquez et al ., ; Signorelli, Márquez & Pastorino, ).…”
Section: Methodsmentioning
confidence: 98%
“…Bivalves often exhibit intraspecific morphological variation in shell shapes between localities (Holme, 1961; Eager et al ., 1984; Márquez & van der Molen, 2011; Signorelli et al ., 2013), habitat types (Zieritz & Aldridge, 2009) and latitude (Beukema & Meehan, 1985). Intraspecific shell shape variation can be used to discriminate populations or stocks (Palmer et al ., 2004; Márquez et al ., 2010, 2017).…”
Section: Introductionmentioning
confidence: 99%